Trend following no mercado brasileiro: propostas de trading systems seguidores de tendências em ativos negociados na BM&FBOVESPA - Santos, Gilcimar Pereira dos (2018)
Trading systems based on trend following strategies are applied by many investors when negotiating in the variable income markets, in operations conducted in several asset classes worldwide. These systems play an important role in investor decision-making process, but still require further study. In this dissertation, four trend following trading systems are presented, whose performances have been demonstrated in order to evaluate their effectiveness in the Brazilian variable income market. Two of the four proposed systems were evaluated in the stock market and the other two were considered for the future contract market. For this purpose, a historical series of asset prices available for trade between January 1995 and December 2014 at the São Paulo Mercantile and Futures Exchange. Through simulations, the systems showed that if they were traded on the stock market and futures markets in Brazil, they would generate profitability, indicating the existence of several trends in the assets studied, obtaining a performance superior to strategy of buying and hold in the market Ibovespa index. This study contributes to the discussion on the effectiveness of trading systems based on the trend following investment philosophy.